Real and Imagined Suburbia: using painting to explore allusions to promise and reality - Harman, Fiona (Curtin University, 2017)
For this practice-led research project, I engage with the fields of contemporary landscape painting and architectural theory to reimagine the display home. Using a method of action research, I use the motifs of suburban architecture and the swimming pool to explore overlapping ideas of promise and reality. My paintings combine abstract and figurative techniques that encourage associative freedom tied to notions of sympathy, feeling, and place.